THE DIFFERENCE IN CRITICAL THINKING SKILLS WITH THE MODEL OF GUIDED DISCO VERY LEARNING (GDL) AND PROBLEM BASED LEARNING (PBL) IN THE BASIC ACCOUNTING SUBJECT FOR CLASS X ACCOUNTING STUDENT IN PUBLIC VHS 46 JAKARTA - Shidiq, Muhammad; Mardi; Sumiati, Ati (Faculty of Economics and Business, Universitas Negeri Jakarta, 2020)
Nowadays, student’s critical thinking skills are still considered low, even though this is really needed in 21st century education. This is because learning is still done classically (lectures), so that students have not been maximized in discover knowledge and solving problems. This research aims to describe of Critical Thinking Skills, Guided Discovery Learning (GDL), problem based learning (PBL), to examine the difference in critical thinking skills with model of Guided Discovery Learning (GDL) and Problem Based Learning (PBL). The research conducted in public VHS 46 Jakarta. The method used in this research is experimental method. The research design used True Experimental Design with Posttest Only Control Design. Data collection techniques using a questionnaire instrument. Hypothesis testing using SPSS 26 shows that the value of Sig. (2-tailed) is 0,021 or smaller than 0,05, it can be concluded that H0 rejected and H1 is accepted. The conclusion from result of this research, there are differences in critical thinking skills with Guided Discovery Learning (GDL) and Problem Based Learning (PBL) in Basic Accounting Subject of Class X Accounting Student in Public VHS 46 Jakarta, which the GDL model has a bigger effect than the PBL model on critical thinking skills.